2015
DOI: 10.1016/j.sbspro.2015.11.581
|View full text |Cite
|
Sign up to set email alerts
|

Effective Techniques for Working with the Tongue Twister in the Elementary Level of Training Russian as a Foreign Language

Abstract: The selection of material for teaching phonetics is a topical problem in the practice of teaching Russian as a foreign language. In this article the tongue twister, as the material for the development of phonetic skills at the elementary level of teaching Russian to foreigners, will be discussed. It is proposed to work only with one tongue twister during daily phonetic exercises. It is also important to organize the work with different types of activities. This paper presents a set of tasks (about 20 exercises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is impossible to estimate how common the actual use of tongue twisters is in teaching, but they seem to be of great importance at least in some countries, for example, in Russia (see Korolkova et al, 2015) and Indonesia, where many of the previous studies referred to in chapter 2 have been conducted. In a study by Szyszka (2016), Polish EFL teachers ( n = 78) indicated the frequency of using tongue twisters in pronunciation teaching on a five‐point scale ( 1 = never, 5 = always ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is impossible to estimate how common the actual use of tongue twisters is in teaching, but they seem to be of great importance at least in some countries, for example, in Russia (see Korolkova et al, 2015) and Indonesia, where many of the previous studies referred to in chapter 2 have been conducted. In a study by Szyszka (2016), Polish EFL teachers ( n = 78) indicated the frequency of using tongue twisters in pronunciation teaching on a five‐point scale ( 1 = never, 5 = always ).…”
Section: Introductionmentioning
confidence: 99%
“…Another idea to support the use of tongue twisters, presented in Korolkova et al (2015), is that they can be viewed as a competitive task, which is something learners usually enjoy and find extra motivation for. Some scholars have, however, expressed criticism toward the tongue‐twister technique.…”
Section: Introductionmentioning
confidence: 99%